Digital height meter using ultrasonic sensor - Wongke, Thunyarat; Awikunprasert, Panatsada; Awikunprasert, Chayanon (Journal of Associated Medical Sciences, 2017)
Introduction: Typical height measurement is to read from scale at the level of observer’s eyes. An error occurs from reading and estimation. Another way is using commercial automatic height meter but quite expensive. Nowadays, Arduino microcontroller board and sensors have been developed and provided an easy way to build a simple, accurate, and cheap a measuring device. Objectives: To design and create a digital height meter that provides an accurate and precise measurement. The digital height meter was measured using ultrasonic sensor with Arduino board. Temperature sensor was added to the circuit to take account on changes of temperature affecting the accuracy of measures. Height of subject was digitally displayed on LCD display. Materials and methods: The first step was to design the circuit and connect ultrasonic sensor and other electronics parts to Arduino board. Equation and code were complied with microcontroller. Efficiency and assessment of the assembled height meter was performed. Height measures were then compared between typical method and the digital height meter. Results: The result showed that efficiency of ultrasonic sensor has an error of 0.6-1.0% for the measurement range of 2-200 cm. Comparison result of three measurement methods, typical measurement, digital height meter with a cardboard, and a digital height meter showed that there was a significant difference between typical height measurement and height meter (p=0.017) with measurement error of 4.0%. However, measurement using height meter with a cardboard has an error of 1.0% and was not different from typical method (p=0.793). After improvement of equation, the results showed that efficient of digital height meter was increased by 2.0%. Conclusion: This digital height meter is easy to construct and cheap. It provides touchless and fast technique to measure height. However, precision and accuracy of the digital height meter depend on performance of the ultrasonic sensor. The more accurate ultrasonic sensor is more expensive. Adding temperature sensor helps to enhance accuracy of measurement. In addition, angle of reflection of the sensor affects accuracy of the measurement.